2014
DOI: 10.2105/ajph.2013.301809
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Health Department Capacity for Health Care–Associated Infection Prevention Through Recovery Act–Funded Programs

Abstract: ARRA-HAI funding substantially improved HD capacity to reduce HAIs not targeted by other national efforts, suggesting that HDs can play a critical role in addressing emerging or neglected HAIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…There is a growing evidence base establishing the efficacy of HAI prevention collaboratives that emphasise health system change through surveillance, data feedback, systematic implementation of prevention measures, and intrafacility and interfacility collaboration 19–21. Other researchers have surveyed DOH about their HAI prevention activities and found that between 2009 and 2011, just prior to our study period, federal funding had resulted in 60 prevention collaboratives 22. Therefore, it is not surprising that we found increased partnerships described by interviewees in all states.…”
Section: Discussionmentioning
confidence: 71%
“…There is a growing evidence base establishing the efficacy of HAI prevention collaboratives that emphasise health system change through surveillance, data feedback, systematic implementation of prevention measures, and intrafacility and interfacility collaboration 19–21. Other researchers have surveyed DOH about their HAI prevention activities and found that between 2009 and 2011, just prior to our study period, federal funding had resulted in 60 prevention collaboratives 22. Therefore, it is not surprising that we found increased partnerships described by interviewees in all states.…”
Section: Discussionmentioning
confidence: 71%
“…During the ELC Recovery Act cooperative agreement, NHSN enrollment increased across the country in large part due to Centers for Medicare and Medicaid Services incentives, whereas state mandates also motivated facilities to enroll in NHSN (Centers for Medicare and Medicaid Services, 2013). The state HAI programs were able to provide technical assistance to facilities for enrollment, getting started with reporting, and more than 55 validation projects (Ellingson et al, 2014). Despite gains made throughout the cooperative agreement relative to surveillance, all respondent types described the need for enhancements.…”
Section: Discussionmentioning
confidence: 99%
“…A conceptual program model was developed by CDC and guided the evaluation serving as the basis for expectations related to health department functioning and performance (Ellingson et al, 2014). The purpose of this model was to elucidate the pathway between the funding distributed to state health departments for HAI prevention and the desired outcome of safer health care.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal obstacles to the development and maintenance of infection control and prevention programmes are the need of an adequate number of trained personnel in the team, and the motivation of employees to attend such courses [24–26]. Hence, it is important to understand the burden of disease and identify points for improvement in each clinical environment in order to establish an optimal programme.…”
Section: Introductionmentioning
confidence: 99%